Frequency of Endometrial Hyperplasia in Premenopausal Women with Heavy Menstrual Bleeding / Abnormal Uterine Bleeding (Medical Forum Monthly, 2024)
Objective: This study was performed with an aim to determine the frequency of different types of endometrial hyperplasia in premenopausal women presenting with menstrual irregularity.Study design: Descriptive / cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Fauji Foundation Hospital, Rawalpindi from September 2011 to March 2012.Materials and Methods: 263 patients aged between 40 to 50years having heavy menstrual bleeding or abnormal uterine bleeding were enrolled in the study using non probability consecutive sampling technique. Transvaginal ultrasound was performed to measure the endometrial thickness which was followed by endometrial sampling, done by pipelle endocurette. Histopathology reports were reviewedResults: Out of263patients,endometrial hyperplasia was diagnosed in 68 patients. The frequency of various types of endometrial hyperplasia i.e. simple hyperplasia without and with atypia, and complex hyperplasia without and with atypia was found to be 60.3%, 17.6%, 14.7% & 7.3% respectively. Mean age of patient in the study was 45.3+ 3.2 years. 91.9% of the patients were multiparous. 67.6% of the patients presented with heavy menstrual bleeding and 32.2% presented with abnormal uterine bleeding.60.2% of the patients have endometrial thickness more than 10mm.Conclusion: Premenopausal women with menstrual irregularity should be evaluated for endometrial hyperplasia as it is precursor for endometrial carcinoma so that early detection and treatment improves their quality of life.